The art and science of communication tools for effective communication in the workplace P.S. Perkins. - Perkins, P. S. 1959- (John Wiley & Sons, 2008)
The Art and Science of Communication shows you a new way to understand and use communication in the workplace. Revealing the seven types of communication we all use every day, the book shows you how to increase your communication effectiveness in any setting with practical techniques, analogies, and models that clearly explain the formulas for successful communication. Combining the science and art of communication into one effective formula, this book offers a straightforward and easy to understand plan for a more successful career